Dyslipidemia, C-reactive protein and leptin levels in non diabetic obese subjects - Lakshmi, Sowbhagya; Ravichand, DM (Bangladesh Liver Journal, 2009)
Introduction: The objective of the study is to find the relationship of obesity with dyslipidemia and Leptin levels. Material and Methods: The study was carried out in the Department of clinical Biochemistry, Bangalore Medical College. Cases and controls were chosen from the subjects attending the out patient department of Victoria hospital for their routine check up.The protocol of the study was to study and compare the linear relationship of obesity, dyslipidemia, CRP and Leptin levels is Non Diabetic obese persons to Non Diabetic persons with normal weight. The protocol was based on inclusion and exclusion criteria and is approved by local ethical committee Serum samples were stored at -200C for estimation of Leptin and CRP levels. The samples were thawed on one stretch for the estimation. Leptin was analyzed by DRG Leptin sand witch ELISA method by using kit from DRG Company. Results: About 8.0% of patients had elevated Total cholesterol in normal subjects when compared to 84.0% in Obese subjects, indicates that patients with obesity are 60.37 times more likely to have elevated Total cholesterol (>200 mg/dl) when compared to Normal. Patients with obesity (98.0%) are 46.23 times more likely to have elevated Triglycerides when compared to normal subjects (52.0%). Subjects in Obese groups, 76.0% had decreased HDL when compared to only 12.0% on Normal group, which 8.14 times more likely in obsess group. Subjects with obesity (80.0%) are 29.33 times more likely to have elevated LDL (>150 mg/dl) when compared to Normal subjects (12.0%). The elevated VLDL is 21.0 times more likely in obese subjects (84.0%) when compared to normal subjects (20.0%). Subjects in obese are 46.58 times more likely to have elevated LP (a) when compared to normal subjects. Conclusions: Present study has shown a strong link between obesity, dislipidemia and cardiovascular disease in accordance with other studies. The role of Leptin associated with cardiovascular disease is not well established, so prospective study should be carried out to elucidate the role of Leptin in cardio vascular disease and Diabetes to establish its role as, whether it is causative, additive risk factor or a protective factor. Leptin may play a role to prevent metabolic syndrome by its interaction with neuroendocrine systems to maintain metabolic homeostasis, similar to the role played by Insulin in homeostasis of blood sugar level. doi: 10.3329/blj.v1i1.2625 Bangladesh Liver Journal Vol.1(1) 2009 p.41-50